PERCEIVED STRESS AND ITS ASSOCIATION WITH POSITIVE MENTAL HEALTH AND ACADEMIC PERFORMANCE OF UNIVERSITY STUDENTS - Safina Khan (Army Medical College Rawalpindi, 2020)
Objective: To investigate the relationship between perceived stress, positive mental health and academic performance among university students.